2017
DOI: 10.7575/aiac.ijalel.v.6n.6p.57
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using Podcast on Listening Comprehension among Iranian Pre-intermediate EFL Learners

Abstract: The purpose of the present study was to explore the effects of using podcast on listening comprehension among Iranian pre-intermediate EFL learners. To fulfill the objectives of the study a Homogeneity test (Oxford Quick Placement Test) was administered among 90 students at the pre-intermediate level of Poyesh language Institute and finally 60 participants were selected. Then, they were non-randomly divided into two sub­groups, namely control and experimental groups.  Before starting the treatment, a validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
3
17
0
1
Order By: Relevance
“…Students and with the growth of technology find that enhancing listening abilities become easier because technological tools allow them to access the suitable videos needed without facing major difficulties because of the availability of authentic materials worldwide and students can listen to and watch a large number of videos to build their listening abilities at the time and place of their choice and as a result move a step forward to being independent learners. The Internet also makes teachers and students encourage the idea of integrating technology inside the language classroom to improve listening provided that schools provide the needed technological equipment (Bohloulzadeh& Rahmatollahi, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students and with the growth of technology find that enhancing listening abilities become easier because technological tools allow them to access the suitable videos needed without facing major difficulties because of the availability of authentic materials worldwide and students can listen to and watch a large number of videos to build their listening abilities at the time and place of their choice and as a result move a step forward to being independent learners. The Internet also makes teachers and students encourage the idea of integrating technology inside the language classroom to improve listening provided that schools provide the needed technological equipment (Bohloulzadeh& Rahmatollahi, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nitekim alan yazındaki çalışmalar incelendiğinde e-dinletilerin dinlediğini anlama başarısına olumlu etki ettiğini belirten birçok çalışma görülmektedir (Abdulrahman, Basalama & Widodo, 2018;Al Fadda & Al Qasim, 2013;NamazianDost, Bohloulzadeh & Rahmatollahi, 2017;Rahimi & Soleymani, 2015;Shiri, 2015). Türkçenin yabancı dil olarak öğretimi alanında e-dinletilerle ilgili sadece bir çalışmaya ulaşılabilmiştir.…”
Section: Journal Of Bayburt Educationunclassified
“…The advantages of using podcast in language learningspecifally to assist students in listening comprehension have been researched, and the results show increase in students listening comprehension (Abdulrahman, Basalama & Widodo, 2018;Al Fadda & Al Qasim, 2013;NamazianDost, Bohloulzadeh & Rahmatollahi, 2017;Rahimi & Soleymani, 2015;Shiri, 2015). In the field of teaching Turkish as a foreign language, only one study could be found on podcasts.…”
Section: Journal Of Bayburt Educationmentioning
confidence: 99%
“…In teaching speaking activity, the teacher gave opportunity to students in making their own podcast. It was some types of student-created podcast in teaching process using podcast (Namaziandost, 2017). It could be challenged for students because students must produce and recorded their voice in the podcast.…”
Section: Students' Perception On the Use Of Podcastmentioning
confidence: 99%